Efektivitas Implementasi Pendekatan Kontekstual dalam Pembelajaran Aqidah Akhlak Materi Berpakaian Sesuai Syariat Islam - Wulandari Wulandari; Wage Wage (Proceedings Series on Social Sciences & Humanities, 2022)
Learning Aqidah Akhlak as one of the lessons that is quite liked. Especially if the subject matter is delivered with an interesting approach. Students enthusiastically and diligently carry out every lesson created by the teacher and are willing to carry out practical activities ordered by the teacher when teaching. For this reason, a teaching approach that meets these requirements is needed. One teaching approach that can be judged to meet the requirements and conceptual framework is the contextual approach. The purpose of this study was to describe the course of learning the moral aqidah material on dressing according to Islamic shari'ah for class X students of SMK Muhammadiyah 1 Ajibarang and to determine the effectiveness of implementing a contextual approach in learning aqidah morals material dressing according to Islamic law for class X students of SMK Muhammadiyah 1 Ajibarang. This research method uses field research, namely the author directly conducts research on the spot to obtain interview data, observation and documentation. Qualitative description is used to present the data, and the type of research used in this study is qualitative descriptive research. This study shows that the effectiveness of the implementation of the contextual approach in learning aqidah morals for class X in dressing according to Islamic law at SMK Muhammadiyah 1 Ajibarang has been going well and has proven to be effective, it can be seen from the results of the assessment carried out by the teacher after the lesson is finished.